Periodontopathogens levels and clinical response to periodontal therapy in individuals with the interleukin-4 haplotype associated with susceptibility to chronic periodontitis - Finoti, L. S. [UNESP]; Anovazzi, G. [UNESP]; Pigossi, S. C. [UNESP]; Corbi, S. C. T. [UNESP]; Teixeira, S. R. L.; Braido, G. V. V. [UNESP]; Kim, Y. J.; Orrico, Silvana Regina Perez [UNESP]; Cirelli, Joni Augusto [UNESP]; Mayer, M. P. A.; Scarel-Caminaga, R. M. [UNESP] (Springer, 2013)
Periodontitis is an inflammatory disease that results from an interaction between dental biofilm agents and the host immune-inflammatory response. Periodontopathogenic organisms, such as Porphyromonas gingivalis, Tannerella forsythia, and Treponema denticola, as well as the host's susceptibility, represented by the host's genetic makeup, are the key factors that influence this complex disease. Recently, we identified haplotypes in the IL4 gene that were associated with chronic periodontitis (CP). This study aimed to evaluate whether subjects with different IL4 haplotypes (TCI/CCI and TTD/CTI) would be differentially colonized by periodontopathogens and whether they would respond differently to non-surgical periodontal therapy. Thirty-nine patients carrying the IL4 haplotype of genetic susceptibility to CP (IL4+) or protection against CP (IL4-) were evaluated. Those groups were further subdivided into individuals with CP (CP IL4+ or CP IL4-) and those that were periodontally healthy (H) (H IL4+ or H IL4-). CP patients were submitted to non-surgical periodontal therapy. Clinical and microbiological analyses were performed considering the data at baseline and 45 and 90 days after periodontal therapy. Periodontopathogens levels were evaluated by absolute quantitative polymerase chain reaction (qPCR). The baseline data revealed that the total levels of periodontopathogens were higher in the CP IL4+ than in the CP IL4- groups. Clinical analyses revealed that the periodontal therapy was equally effective, independent of the subject's IL4 genetic load. The TCI/CCI IL4 haplotype, previously associated with genetic susceptibility to CP, was also associated with increased levels of periodontopathogenic bacteria, but this genetic background did not influence the response to non-surgical periodontal treatment.